Exploration of Constitutional Bias and Associated Factors in Patients with Recurrent and Metastatic Gastric Cancer, and the Therapeutic Effect of Prescription: A one-arm study - Luchang Cao; Xinmiao Wang; Xinyi Ma; Guanghui Zhu; Jie Li (Integrative Cancer Therapies)
Objective: This study was conducted to elucidate the distribution characteristics of predominant unbalanced constitutions and TCM syndrome elements in patients with recurrent and metastatic gastric cancer. This study was also undertaken to analyze the potential relationship between the body constitutions of patients, syndrome elements, and biological indicators, as well as to investigate the effect of Yiqi Wenyang Jiedu prescription (YWJP) on symptoms and biological indicators before and after treatment. Result: Yang -deficiency and Qi -deficiency were identified as prevalent imbalanced constitutions among patients with recurrent and metastatic gastric cancer. The primary syndrome factors associated with disease localization included the spleen-stomach and liver, with the main syndrome elements being Qi -deficiency, Yang -deficiency, and Qi -stagnation. Patients with Qi -deficiency and Yang -deficiency constitutions exhibited lower BMI and higher monocyte-to-lymphocyte ratio (MLR). A notable positive correlation was observed between cold ( Yang -deficiency) and BMI, as well as between Qi -deficiency constitution and neutrophil-to-lymphocyte ratio (NLR). Furthermore, YWJP demonstrated efficacy in alleviating symptoms associated with Qi -deficiency and Yang -deficiency in patients with recurrent and metastatic gastric cancer, including dyspnea, fatigue, diaphoresis, cold intolerance, abdominal sounds, postural changes, and abdominal distension. Discussion: Yang -deficiency and Qi -deficiency emerged as prevalent constitutional patterns in patients with recurrent and metastatic gastric cancer. Notably, BMI, MLR, and NLR may serve as physiological indicators of these conditions. Furthermore, YWJP treatment demonstrated potential efficacy in alleviating symptoms associated with Qi -deficiency and Yang -deficiency in this patient population. Clinical Trial Registration: Chinese Clinical Trial Registry: ChiCTR2200055826.